Prophylaxis of macular edema after cataract surgery in diabetic patients, topical Nepafenac versus intravitreal Ranibizumab. Issue 1 (January 2022) - Howaidy, Ahmed; Eldaly, Zeiad H; Anis, Mohamed; Othman, Tageldin M
Purpose: To compare effect of topical Nepafenac versus intravitreal Ranibizumab on macular thickness after cataract surgery in diabetic patients with no preoperative macular edema. Patients and methods: A prospective randomized controlled study recruited diabetic patients with visually significant cataract and no diabetic macular edema (DME). Patient underwent uncomplicated phacoemulsification with IOL implantation and were randomly assigned to receive post-operative topical Nepafenac, intra-operative intravitreal Ranibizumab, or no prophylactic treatment. Changes in subfoveal and perifoveal macular thickness were assessed by SD-OCT. Results: The mean central macular thickness showed a significant increase in all study groups 1 week and 1 month postoperative when compared to baseline. At 3 months postoperative, there was a significant difference between Nepafenac and Control group ( p  = 0.017), Ranibizumab and Control groups ( p  = 0.009) with no significant difference between Nepafenac and Ranibizumab group ( p  = 0.545) regarding CMT. Comparable results could be detected as regarding peri-foveal macular thickness changes. Concerning BCVA, there was a significant difference between topical Nepafenac/control ( p  = 0.001) and intravitreal Ranibizumab/control ( p  = 0.004) at 1-week visit. No significant difference in BCVA was observed between Nepafenac and Ranibizumab group throughout the whole study period. In postoperative visits, cystoid macular edema occurred in three patients (7.9%) in Nepafenac group, one patient (2.7%) in Ranibizumab group, and seven patients (17.07%) in control group. Conclusion: Both postoperative topical Nepafenac and intra-operative intra-vitreal Ranibizumab are effective adjunctive to phacoemulsification in diabetic patients for prophylaxis of macular edema.